In vivo identification of small molecules mediating Gpr126/Adgrg6 signaling during Schwann cell development. Issue 1 (16th September 2019) - Bradley, Ethan C.; Cunningham, Rebecca L.; Wilde, Caroline; Morgan, Rory K.; Klug, Emma A.; Letcher, Sophia M.; Schöneberg, Torsten; Monk, Kelly R.; Liebscher, Ines; Petersen, Sarah C.
Abstract: Gpr126/Adgrg6, an adhesion family G protein–coupled receptor (aGPCR), is required for the development of myelinating Schwann cells in the peripheral nervous system. Myelin supports and insulates vertebrate axons to permit rapid signal propagation throughout the nervous system. In mammals and zebrafish, mutations in Gpr126 arrest Schwann cells at early developmental stages. We exploited the optical and pharmacological tractability of larval zebrafish to uncover drugs that mediate myelination by activating Gpr126 or functioning in parallel. Using a fluorescent marker of mature myelinating glia ( Tg[mbp:EGFP‐CAAX] ), we screened hypomorphic gpr126 mutant larvae for restoration of myelin basic protein ( mbp ) expression along peripheral nerves following small molecule treatment. Our screens identified five compounds sufficient to promote mbp expression in gpr126 hypomorphs. Using an allelic series of gpr126 mutants, we parsed the ability of small molecules to restore mbp, suggesting differences in drug efficacy dependent on Schwann cell developmental state. Finally, we identify apomorphine hydrochloride as a direct small molecule activator of Gpr126 using combined in vivo/in vitro assays and show that aporphine class compounds promote Schwann cell development in vivo . Our results demonstrate the utility of in vivo screening for aGPCR modulators and identify small molecules that interact with the gpr126 ‐mediated myelination program. Abstract : Gpr126/Adgrg6 is an adhesion family G protein–coupled receptor (aGPCR) required for the development of myelinating Schwann cells in the peripheral nervous system. In mammals and zebrafish, mutations in Gpr126 arrest Schwann cells at early developmental stages. The authors of this article used larval zebrafish to uncover drugs that mediate myelination by activating Gpr126 or functioning in parallel.